A cross-sectional study on the knowledge of and interest in Planetary Health in health-related study programmes in Germany - Klünder, Vera; Schwenke, Paula; Hertig, Elke; Jochem, Carmen; Kaspar-Ott, Irena; Schwienhorst-Stich, Eva-Maria; Stauch, Lisa; Coenen, Michaela (Frontiers in Public Health, 2022)
Planetary Health connects human health with the natural and anthropogenic systems on which it depends. Planetary Health education has been growing in a wide range of health-related disciplines, yet not been widely implemented in health-related university curricula. This cross-sectional study focused on students’ knowledge of and interest in Planetary Health education in order to assess the relevance of Planetary Health and Planetary Health topics for university students and their fields of study. We surveyed 1,303 students enrolled in health-related programmes in Bavaria, Germany. Data was collected on students’ previous knowledge of and interest in Planetary Health, as well as the relevance of different Planetary Health topics and students’ willingness to select a Planetary Health elective within their study programmes. Descriptive statistics were calculated. The majority of participants (73.8%) had not yet heard of Planetary Health but were interested in learning more about this field (90.7%). Most participants considered Planetary Health as relevant to their field (81.6%) and would likely choose a Planetary Health elective (81.9%). Participants were most interested in topics about general associations between climate and health as well as its connections with mental health and (micro)plastics. There is an urgent need and high student interest to implement a Planetary Health module in health-related study programmes in order to move this topic more into focus for the next generation of students.